2022
DOI: 10.1080/21655979.2022.2084498
|View full text |Cite
|
Sign up to set email alerts
|

Prodigiosin: a promising biomolecule with many potential biomedical applications

Abstract: Pigments are among the most fascinating molecules found in nature and used by human civilizations since the prehistoric ages. Although most of the bio-dyes reported in the literature were discovered around the eighties, the necessity to explore novel compounds for new biological applications has made them resurface as potential alternatives. Prodigiosin (PG) is an alkaloid red bio-dye produced by diverse microorganisms and composed of a linear tripyrrole chemical structure. PG emerges as a really interesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 169 publications
0
11
0
Order By: Relevance
“…Strains of RPPS widely spread along the tissues of infested palms. Extensive studies have reported the antimicrobial activity of prodigiosin [ 278 , 279 ]. This finding is consistent with the antibacterial activity shown by RPPS strains collected from RPW vs. both Gram-positive ( Bacillus sp., Paenibacillus sp., Lysinibavillus sp.…”
Section: Bacteria Symbionts Of Red Palm Weevilmentioning
confidence: 99%
“…Strains of RPPS widely spread along the tissues of infested palms. Extensive studies have reported the antimicrobial activity of prodigiosin [ 278 , 279 ]. This finding is consistent with the antibacterial activity shown by RPPS strains collected from RPW vs. both Gram-positive ( Bacillus sp., Paenibacillus sp., Lysinibavillus sp.…”
Section: Bacteria Symbionts Of Red Palm Weevilmentioning
confidence: 99%
“…Prodigiosins are natural products isolated from microorganisms and possess potent immunosuppressive, antimicrobial, antimalarial, and cytotoxic properties. [1][2][3] These are pyrrolyldipyrrins which are a sub-class of dipyrrins extended through the incorporation of a pyrrole at the 9-position. To enhance the cytotoxicity and improve toxicological profiles, a lot of attention has been focused on preparing prodigiosin derivatives 2a containing substituents or functional groups on any of the three-pyrrole rings.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the phylum Actinomycetota, considered the most prolific bacterial source of drug-lead chemicals ( Bahrami et al, 2022 ), have also been reported to synthetize prodigiosins. From several species of Streptomyces ( S. longisporuber , Streptomyces griseoviridis and S. coelicolor ), Actinomadura ( Actinomadura madurae and A. pelletieri ), and from Streptoverticillium rubrireticuli , undecylprodigiosin, butylcycloheptylprodigiosine, metacycloprodigiosin, nonylprodigiosin, prodigiosin 25-C and prodigiosins R1, R2 and R3 were described, highlighting actinobacterial metabolism richness in the production of these tripyrrole red pigments ( Harashima et al, 1967 ; Gerber, 1969 ; Gerber, 1975 ; TSAO et al, 1985 ; Kawasaki et al, 2008 ; Kimata et al, 2018 ; Islan et al, 2022 ; Kimata et al, 2023 ). The widespread occurrence of prodigiosins in phylogenetically distant microbes suggests that these molecules may play a significant, albeit uncertain and yet to be fully defined, physiological role.…”
Section: Introductionmentioning
confidence: 99%